O efeito da fotobiomodulação na fadiga e sintomas referidos em indivíduos com esclerose múltipla remitente recorrente– estudo piloto - Alencar, Raquel Candido (2019)
Multiple sclerosis is an autoimmune disease of the central nervous system, characterized by inflammation and destruction of the myelin sheath. Fatigue is one of the main symptoms noticed by patients, impacts with quality of life and has few treatment options. Photobiomodulation is used in a variety of inflammatory conditions and may be beneficial in the treatment of multiple sclerosis fatigue. Objective: To conduct a pilot study to analyze the effect of photobiomodulation in the treatment of fatigue and symptoms reported by patients with recurrent remitting multiple sclerosis. Method: Participants was recruited from UNINOVE integrated health outpatient clinic, randomized and allocated into two groups: Group 1, sublingual application; Group 2, radial artery application. Fatigue was analyzed by the modified fatigue impact scale. In addition, each participant described which more limiting symptoms they had over the past 3 months and which ones observed improvement in the last days. The protocol was performed twice a week for 3 months. Results: Modified fatigue impact scale scores showed significant reduction after treatment in group 1 (p <0.05) and slight decrease in group 2 (p> 0.05), analysis by the Mann-Whitney test. The mentioned symptoms in the evaluations was fatigue, headache, muscle pain and paresthesia. Of these, fatigue and muscle pain showed significant improvement (p <0.05) after treatment. Conclusion: Photobiomodulation could be a viable resource in the management of fatigue in people with recurrent remitting multiple sclerosis, because the applied in the sublingual region significantly decreased the scores of the assessment scale used and both applications decreased the fatigue reported by patients, although muscle pain, headache and paresthesia did not improve with the proposed treatment.